PENGEMBANGAN MEDIA PETUALANGAN MATEMATIKA (PETAMATIKA) PADA MATERI KELILING DAN LUAS BANGUN DATAR UNTUK KELAS IV SEKOLAH DASAR - Karnen, Dini Fitria Sari (universitas Ahmad Dahlan, 2020)
This study aims to determine the development procedures and determine the feasibility of the Petulangan Matematika (Petamatika) media.. This research is a type of Research and Development (R&D) used the Borg and Gall development model with the following stages: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revisions, (6) main field testing (small-scale), (7) operational product revisions and (8) operational field testing (large-scale). The trial subjects used were 27 students in IV grade and teachers in Muhammadiyah Tamantirto Elementary School. Data collection techniques in the form of interviews, observation and questionnaires. Data analysis includes quantitative data analysis and qualitative data analysis. The results showed that the validation of the media experts scored 78.33 in the